Predictors of early mortality after transcatheter aortic valve implantation - Kjønås, Didrik; Dahle, Gry; Schirmer, Henrik; Malm, Siri; Eidet, Jo; Aaberge, Lars; Steigen, Terje; Aakhus, Svend; Busund, Rolf; Rösner, Assami (Open Heart, 2019)
Objectives - To investigate whether preoperative echocardiographic evaluation of ventricular function, especially right ventricular systolic and diastolic parameters including speckle-tracking analysis, could aid in the prediction of 30-day mortality after transcatheter aortic valve implantation (TAVI) in patients with aortic stenosis. Methods - This is a prospective observational cohort study including 227 patients accepted for TAVI at the University Hospital of North Norway and Oslo University Hospital from February 2010 through June 2013. All patients underwent preoperative transthoracic echocardiography with retrospective speckle-tracking analysis. Primary endpoint was all-cause 30-day mortality. Results - All-cause 30-day mortality was 8.7 % (n = 19). Independent predictors of 30-day mortality were systolic pulmonary arterial pressure (SPAP) > 60 mm Hg (HR: 7.7, 95% CI: 1.90 to 31.3), heart failure (HR: 2.9, 95% CI: 1.1 to 7.78), transapical access (HR: 3.8, 95% CI: 1.3 to 11.2), peripheral artery disease (HR: 6.0, 95% CI: 2.0 to 18.0) and body mass index (HR: 0.73, 95% CI: 0.61 to 0.87). C-statistic for the model generated was 0.91 (95% CI: 0.85 to 0.98). Besides elevated SPAP, no other echocardiographic measurements were found to be an independent predictor of early mortality. Conclusion - Except for elevated systolic pulmonary artery pressure, our data suggests that clinical rather than echocardiographic parameters are useful predictors of 30-day mortality after TAVI.